In situ transformation boosts the pseudocapacitance of CuNi-MOF via cooperative orientational and electronic governing. Issue 6 (3rd June 2023) - Chu, Xianyu; Meng, Fanling; Zhang, Wei; Zhang, Lihua; Molin, Sebastian; Jasinski, Piotr; Zheng, Weitao
Abstract : The disordered arrangement and thereof inferior conductivity of 2D MOF sheets seriously hinder their practical application. Herein, we propose in situ transformation strategy to architect vertically oriented bimetallic CuNi-MOF as a self-supporting electrode, leading to a decuple high specific capacitance of 1262 C g -1 in comparison with the pristine Ni-MOF powder of 114 C g -1 at 2 A g -1 . DFT calculations reveal that introduction of Cu can modulate the electronic structure of metal centers in the Ni-MOF sheets and optimize electrical conductivity. Our strategy is promising to maximize the utilization of MOF superiorities for optimizing their electrochemical performance. IMPACT STATEMENT: We provide an in situ transformation strategy for synthesizing high-activity oriented bimetallic MOFs derived from vertically oriented Cu(OH)2 nanowires, with which an order of magnitude of performance-improved electrodes were produced for pseudocapacitance.